The Homo Oeconomicus Paradigm in the Context of Behavioural Accounting - Mazurowska, Marta (Studia Oeconomica Posnaniensia, 2014)
The changes that are currently taking place in economic science also affect accounting. The purpose of this article is to present the idea of behavioural accounting as a trend which has been developing in response to the changes in assumptions that form the basis of economics. The specified objective was achieved through conducting a critical analysis of national and international developments in the fields of economic science, including accounting and behavioural science. The text presents the main theses as well as a critique of the homo oeconomicus paradigm which has resulted in the popularisation a behavioural trend in economics, including accountancy.